Effects of polyphosphates and fluoride on hydroxyapatite dissolution: A pH-stat investigation - Do Amaral, Jackeline Gallo [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP]; Pessan, Juliano Pelim [UNESP]; Manarelli, Michele Mauricio [UNESP]; Barbour, Michele E. (Elsevier, 2016)
Objectives: This study investigated the immediate and sustained effect of sodium trimetaphosphate (TMP) and sodium hexametaphosphate (HMP) associated or not with fluoride (F) on hydroxyapatite (HA) dissolution using an erosion-like model, considering as well as the influence of salivary coating. Design: Baseline dissolution rates were determined for HA discs using a pH-stat system. In the first set of experiments, HA discs were treated with 1100 μg F/mL, 1% or 8% of HMP, 1% or 8% of TMP and 1100 μg F/mL associated with 1% or 8% of HMP or TMP, totaling 9 groups (n = 8). In a second phase, HA discs were kept in pooled human saliva at 37 °C for 2 h before treatment with deionised water and 1100 μg F/mL associated with 1% or 8% of HMP or TMP, totaling 5 groups (n = 8). The post-treatment dissolution rate was determined from three consecutive 30-min assays. Data were analysed using 2 and 3-way ANOVA followed by Fisher and Holm-Sidak methods, respectively (α = 0.05). Results: All test solutions promoted reduction in HA dissolution rate when compared to baseline control in the first post-treatment run (p < 0.001). However, a synergistic effect was only observed between fluoride and 1% HMP. Moreover, the duration of inhibitory effect was greater when 8% HMP and 1 or 8% HMP associated with F were assessed (p < 0.001). The presence of salivary coating led to higher protection for all groups when compared to discs without coating (p < 0.001). Conclusion: The reduction of HA dissolution rate, as well as the duration of this effect were influenced by fluoride, type and concentration of phosphate salt and the presence of a salivary coating.
Keywords: Erosion; Fluoride; Hydroxyapatite; Polyphosphates; Salivary coating